APPLICATION OF SUMMARIZED FUNCTIONS FOR INFORMATION SOURCE PROTECTION - Dzhurov, Valerij (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Probing signals are succession of impulses with defined frequency and amplitude. The succession itself could be “masked” using changing functions (from the main carrying) under specific laws. The sequence of impulses could be described by summarized functions of different type.